2017
DOI: 10.5483/bmbrep.2017.50.11.179
|View full text |Cite
|
Sign up to set email alerts
|

Rules for functional microRNA targeting

Abstract: MicroRNAs (miRNAs) are ~22nt-long single-stranded RNA molecules that form a RNA-induced silencing complex with Argonaute (AGO) protein to post-transcriptionally downregulate their target messenger RNAs (mRNAs). To understand the regulatory mechanisms of miRNA, discovering the underlying functional rules for how miRNAs recognize and repress their target mRNAs is of utmost importance. To determine functional miRNA targeting rules, previous studies extensively utilized various methods including high-throughput bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…MiRNA is a type of endogenous non-coding single-stranded RNA molecule of 18-22 nt in length that can degrade or inhibit translation by specific binding to the 3'UTR region of the target mRNA, and it also plays an important regulatory role in the biological processes of cell growth, differentiation, embryonic development and immune response [9]. According to previous reports [10][11][12], 2588 mature miRNAs have been identified in the human body, and each miRNA can widely participate in various life activities of the human body, and regulate the occurrence and development of diseases and cancers.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA is a type of endogenous non-coding single-stranded RNA molecule of 18-22 nt in length that can degrade or inhibit translation by specific binding to the 3'UTR region of the target mRNA, and it also plays an important regulatory role in the biological processes of cell growth, differentiation, embryonic development and immune response [9]. According to previous reports [10][11][12], 2588 mature miRNAs have been identified in the human body, and each miRNA can widely participate in various life activities of the human body, and regulate the occurrence and development of diseases and cancers.…”
Section: Discussionmentioning
confidence: 99%
“…us, it is critical to understand the molecular mechanisms of ESCA and explore reliable prognostic biomarkers. A large number of studies have reported that miRNAs could play a crucial role in cancer by functioning as oncogenes or tumor suppressor genes [18]. Moreover, it has been demonstrated that the miRNA profile of tissues exhibits characteristic changes in certain types of tumors [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The first miRNA genes known as lin-4 and let-7 and their role as post-transcriptional regulators of gene expression were described in Caenorhabditis elegans during the early 1990s [ 81 , 82 ]. Micro RNAs are small, ncRNA molecules of ~22 nucleotides in length that use short regions of complementarity of around six to eight nucleotides of their target mRNAs to repress gene expression [ 83 , 84 ]. Endogenous miRNA-complementary sites are located within the 3′ and 5′ untranslated regions (3′ and 5′ UTRs) of target mRNAs as well as in the coding sequence [ 85 , 86 , 87 ].…”
Section: Non-coding Rnasmentioning
confidence: 99%